Designing Website-Based Administration Management Information System - Khoirunnisa, Nurfitria; Haryati, Haryati; Jubaedah, Eulis; Rostiawati, Tia (CV. Generasi Intelektual Digital, 2023)
Administration is one of the essential things for the running of an organization. If in an organization the administrative management is good, the organization will also be able to run well. The current administration can be used for decision-making, evaluating the activities carried out, and even knowing whether or not the organization is being run. The same happened at the Informatics Management Student Association (HIMMI) at the Subang State Polytechnic campus. Administrative management that is carried out is still conventional by storing documents in several storage folders so that there is a buildup of documents. Even documents will be scattered everywhere. Making letters is still done by checking the last number on the general ledger, so it has difficulty to make letter numbers. The submission of letters is hampered because it takes a long time because goes through a fairly long flow. Therefore, a solution was found, namely the Design of a Website-Based Administration Management Information System using the Waterfall method to assist secretaries in managing secretarial administration at the Informatics Management Student Association. The result obtained is an administrative management information system that can facilitate the storage of documents that have been integrated with the database. In addition, the system can simplify the process of issuing outgoing letters, overcome the problem of double mail numbering, streamline the attendance process, provide a timeline of work programs, and can provide information related to the reports needed. The test results conducted using the black-box testing method on 102 test items were declared 100% valid. It showed no errors or failures in the system at the time of running.